Light Control and Watering System in Greenhouse for The Cultivation of Chrysanthemum Sp - Adam Faroqi; Muhammad Ali Ramdhani; Muhammad Fahmi Amrillah; Lia Kamelia; Eneng Nuraeni (Institute of Advanced Engineering and Science, 2018)
Chrysanthemum (Chrysanthemum Sp) is sensitive to temperature and humidity. The greenhouse is an appropriate planting medium since temperature and humidity can be engineered there. This article presents the design of systems using DHT-22 and SEN0057 sensors. Real Time Clock (RTC) is used for providing timing input and functions as an extra light intensity timer. Arduino Mega 2560 is used as a microcontroller functioning to receive the results of sensor measurement and to give output instructions to condition the temperature and humidity. The testing on chrysanthemum Sp placed inside the greenhouse equipped with the system for 7 days shows an increase of height of 3.7 cm. As for chrysanthemum Sp placed outside the greenhouse equipped with the system for 7 days, there is an increase of height of 0, 2 cm. These greenhouse light control and Watering systems can engineer the temperature and humidity in accordance with the needs of chrysanthemum Sp cultivation in the greenhouse.